A Quantum Chemical Study on Structure of 1,2-Bis(diphenyl-phosphinoyl) ethane and 4-chlorophenol cocrystal - YENIKAYA, CENGIZ; POYRAZ, MEHMET; CEVIK, SABRI (Asian Journal of Chemistry, 2010)
The cocrystal of 1,2-bis(diphenylphosphinoyl)ethane (DPPEO) with 4-chlorophenol (1:2) were studied theoretically with MINDO/ 3, MNDO, PM3 and AM1 semi empirical methods to elucidate its structure. The bond lengths and angles from theoretical studies of molecule DPPEO/4-chlorophenol (1:2) were found to be as expected. Theoretical results, concerning with intermolecular van der Waals forces in cocrystal, were compared with the previously obtained experimental data and AM1 results were found to be the best fit for selected C-C, C-P and P-O bond lengths and angles of DPPEO/4-chlorophenol. For the hydrogen bond geometry none of the theoretical methods were found to be comparable with experimental data.